Bacteria in agrobiology : plant probiotics - Maheshwari, Dinesh K (Springer Berlin Heidelberg, 2012)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. "Bacteria in Agrobiology: Plant Probiotics" discusses the current trends and future prospects of beneficial microorganisms acting as Probiotics. Topics include the application for the aboveground fitness of plants, applications in mountain ecosystems, in tropical and Mediterranean forests, and in muga sericulture. Further aspects are Arabidopsis as a model system for the diversity and complexity of plant responses, plant parasitic nematodes, nitrogen fixation and phosphorus nutrition.